dGIPC is required for the locomotive activity and longevity in Drosophila. - Kim, J.; Lee, S.; Ko, S.; Kim-Ha, J. (Biochemical and Biophysical Research Communications, 2010)
To identify genes that function in the adult neural system, we screened pools of P element-mediated mutants and tested locomotor activity of homozygous flies. Of 1014 P element-mutagenized lines, 638 were homozygous viable. These lines were tested for climbing ability and lifespan. We isolated dGIPC, a Drosophila homolog of GIPC, that produced a 50% premature loss of locomotor activity and a 30% reduction in life span. We found that dGIPC is expressed in the central brain of adult flies, especially in glia and dopaminergic (DA) neurons. Inhibition of dGIPC expression in DA neurons significantly affected climbing ability and survival. In vertebrates, interactions between GIPC with dopamine receptors have been reported. Our findings, together with those obtained from vertebrate models, suggest that DrosophiladGIPC acts in the adult central nervous system and may be required to regulate the trafficking of dopamine receptors needed for proper functioning of dopaminergic neurons.